ANALISIS EFEKTIVITAS MODEL PEMBELAJARAN DALAM MENINGKATKAN PEMAHAMAN KONSEP SISWA PADA PELAJARAN IPA SMP NEGERI 1 TUHEMBERUA - GEA, SEPI FITA SARI; WARUWU, TOROZIDUHU; ZEGA, NOVELINA ANDRIANI; WARUWU, YAREDI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT This research was motivated by students who were not actively involved in learning, teachers who still used lecture learning methods, and students' lack of understanding of concepts in learning. The type of research used is a qualitative descriptive approach. The research location is at SMP Negeri 1 Tuhemberua. The research population is class IX students in the odd semester of the 2024/2025 academic year. Research instruments, namely: observation sheet on the effectiveness of the learning model, observation sheet on understanding concepts, and learning outcomes tests. Research results: (1) The effectiveness of the learning model in science learning at SMP Negeri 1 Tuhemberua was discovered that at Meeting 1 the percentage was 66.91% with